HYPERLACTATEMIA AS PREDICTOR MORBIDITY IN ACUTE MYOCARDIAL INFARCTION - Bagiari, Ketut Erna; Rina, Ketut; Iswari, Ida Sri (Medicina, 2016)
Acute myocardial infarction (AMI) still have high prevalence of morbidities and mortality, and thereforewe need a reliable marker that represent the severity of the disease. Degree of hypoperfusion canmeasure by lactate production. Lactate is a byproduct of anaerob metabolism and marker of tissuehypoperfusion.The prognostic role of lactate for morbidity in patients with AMI has not been elucidatedso far. There is no previous study to determine the role of hyperlactatemia as predictor of morbidity inAMI patients in Indonesia.The aim of this study was to assess whether lactate is an independentprognostic predictor morbidity patient with AMI in Sanglah Hospital, Denpasar. This was anobservational cohort prospective study, which enrolled 70 AMI patients by consecutive sampling. Wemeasured capillary lactate level three times, at first admission, 2h, and 24 h after admission, usingrapid point-of-care analyzer accutrend lactatemeter. We observed for morbidities and the subsets(cardiogenic shock, heart failure, arrhythmia) during hospitalization. The result of this study were theAMI patients with hyperlactatemia have an almost 3-fold [hazard ratio (HR) =2.578,95%confidenceinterval (CI)=1.278 to 5.199, P=0.008)increased risk of morbidity, a 15-fold increased risk ofcardiogenicshock of(HR =15.231, 95% CI =1.848 to 700.579,P=0.0014) and a 5-fold increased risk of heart failure(HR=5.269, 95% CI =1.913 to 15.796,P=0.0002) compared with subject without hyperlactatemia. Onthe other hand, hyperlactatemia was not associated as a predictor of arrhythmia (HR = 1.35, 95% CI =0.344 to 4.627,P=0.3051).Hyperlactatemia is an independent predictor of morbidity, cardiogenic shock,and heart failure in AMI patients. On the other hand, hyperlactatemia is not an independent predictorof arrhythmia in AMI patients. [MEDICINA 2015;46:71-6]. Prevalensi morbiditas dan mortalitas pada infark miokard akut (IMA) masih cukup tinggi, dengandemikian dibutuhkan biomarker yang reliabel menggambarkan keparahan penyakit. Derajat hipoperfusidapat dinilai dengan mengukur produksi laktat.Laktat merupakan produk metabolisme anaerob danpenanda hipoperfusi jaringan. Peran laktat sebagai prognosis morbiditas pada pasien IMA hinggasaat ini belum diketahui. Hingga saat ini belum ada studi untuk menentukan peran hiperlaktasemiasebagai prediktor morbiditas IMA di Indonesia. Studi ini dilakukan untuk menilai apakah laktatsebagai prediktor independen prognosis morbiditas pasien IMA di Rumah Sakit Sanglah, Denpasar.Penelitian ini merupakan studi observasional kohort prospektif yang melibatkan 70 pasien IMA dengancara konsekutif. Dilakukan tiga kali pemeriksaan kadar laktat kapiler secara serial yaitu saat pertamakali masuk rumah sakit, 2 jam, dan 24 jam setelahnya dengan menggunakan alat analisis cepataccutrend lactatemeter. Selama perawatan diamati adanya morbiditas, syok kardiogenik, gagal jantung,dan aritmia. Pada penelitian didapatkan hiperlaktasemia pada pasien IMA merupakan prediktormorbiditas risiko hampir 3 kali lipat (HR =2,578,IK 95% = 1,278 sampai 5,199, P=0,008), prediktorsyok kardiogenik sebesar 15 kali lipat (HR =15,231, IK 95% = 1,848 sampai 700,579,P=0,0014) danprediktor gagal jantung 5 kali lipat (HR=5,269, IK 95% = 1,913 sampai 15,796,P=0,0002) dibandingkanpasien tanpa hiperlaktasemia. Hiperlaktasemia tidak terbukti sebagai prediktor aritmia(HR = 1,35,IK 95% = 0,344 sampai 4,627, P=0,3051).Hiperlaktasemia merupakan prediktor independen morbiditas,syok kardiogenik, dan gagal jantung pada pasien IMA. Hiperlaktasemia tidak terbukti sebagai prediktorindependen aritmia pada pasien IMA. [MEDICINA 2015;46:71-6].
Keywords: acute myocardial infarction, hyperlactatemia